Fluorine-doped long-life dual-afterglow carbon dot-based composite material and preparation method thereof

By doping fluorine atoms on the carbon dots and using boric acid as the coating matrix, a carbon dot-based composite material with long-life double afterglow characteristics was prepared, which solved the problem that existing carbon dots are easily imitated and have short afterglow life in anti-counterfeiting applications, and achieved more efficient photoelectric performance.

CN119614190AActive Publication Date: 2025-03-14TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411865552.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing room temperature phosphorescence carbon dots are easily imitated in anti-counterfeiting applications, and their remaining gloss life is short, which cannot meet the needs of multiple encoding anti-counterfeiting and long afterglow display of complex optical signals.

Method used

Fluorine-doped carbon dots and boric acid are used as the coating matrix to prepare fluorine-doped long-life double-afterglow carbon dot matrix composite material by solvothermal method to achieve uniform coating and efficient luminescence of carbon dots.

Benefits of technology

The material exhibits the dual afterglow characteristics of room temperature phosphorescence and delayed fluorescence at different excitation wavelengths, with a delayed fluorescence lifetime of 1.21s, and is suitable for optoelectronic devices, graphics anti-counterfeiting and information encryption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614190A_ABST
    Figure CN119614190A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorine-doped long-life dual-afterglow carbon dot-based composite material with room-temperature phosphorescence and thermally activated delayed fluorescence and a preparation method thereof, folic acid is used as a carbon source, ammonium fluoride is used as a doping agent, fluorine-doped carbon dots are prepared in an ethanol solvent by a solvothermal method, boric acid is used as a coating matrix, and the fluorine-doped long-life dual-afterglow carbon dot-based composite material with room-temperature phosphorescence and thermally activated delayed fluorescence is prepared. And uniformly dispersing in an aqueous solution and reacting to obtain the composite material. The double-afterglow carbon dot-based composite material emits blue fluorescence under the irradiation of 265 nm ultraviolet light, and generates blue delayed fluorescence after the irradiation is stopped; blue fluorescence is emitted under 365nm ultraviolet irradiation, green phosphorescence is generated after irradiation is stopped, and the fluorescent material can be used as an afterglow material to be applied to the fields of photoelectric devices, safety, counterfeiting prevention and the like by utilizing the afterglow property of the fluorescent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of long afterglow luminescent materials, and relates to a photoinduced long afterglow luminescent material based on carbon dots, in particular to a double afterglow carbon dot-based composite material which can emit phosphorescence and delayed fluorescence at room temperature and has a long life, and a method for preparing the carbon dot-based composite material. Background Art

[0002] Carbon dots (CDs), as a new type of nanocarbon material, not only have excellent optical properties, but also have the advantages of simple preparation, low cost and low toxicity, and have attracted widespread attention.

[0003] Due to the unique internal electronic structure and surface chemical reaction of CDs, they emit visible light after being excited by a light source, namely fluorescence and afterglow. Afterglow emission includes room temperature phosphorescence (RTP) and delayed fluorescence (DF). S 1) Transformed into triplet excitons via intersystem crossing (ISC), and then triplet excitons radiatively transition to the ground state ( S 0), RTP is generated; the exciton is transferred from the triplet state ( T 1) to S 1 returns to the ground state through reverse intersystem crossing (RISC) to produce DF. DF materials have a small singlet-triplet energy level difference (Δ E ST ), which can theoretically achieve 100% exciton utilization, greatly improves its exciton utilization compared to fluorescence (FL) which is limited by spin exciton statistics. At the same time, its lifetime is longer than fluorescence, and it has the characteristic of increasing emission intensity with increasing temperature in a certain temperature range. The unique luminescence properties of this type of material make it advantageous in anti-counterfeiting applications.

[0004] At present, RTP CDs are divided into two types: matrix-based RTP CDs and matrix-free RTP CDs, which are mainly used in the fields of anti-counterfeiting and long afterglow display. For example, Zhang et al. (Zhang H, Sun L, Guo X, et al. Applied Surface Science , 2023, 613: 155945.) By printing the prepared C-CDs@SA on filter paper, a green RTP visible to the naked eye for 1 second can be observed. This property can be effectively used for information encryption and anti-counterfeiting. At the same time, C-CDs@SA powder also has important applications in fingerprint detection. Wu et al. (Wu Y, Fang X, Shi J, et al. Chinese Chemical Letters,2021, 32(12): 3907-3910.) The synthesized carbon dots with fluorescent and room temperature phosphorescent optical properties are applied to anti-counterfeiting. The directly screen-printed encoded information and patterns are invisible to the naked eye under natural light. Under different wavelength excitation and removal, clear multi-color patterns with tunable FL and RTP emission are realized for anti-counterfeiting applications. Shi et al. (Shi H, Wu Yang, Xu J,et al. Chemical Engineering Journal , 2023, 476: 146524.) By forming a covalent network on the surface of AP-CDs, the vibration and rotation of the surface emitter are restricted, the non-radiative transition of the triplet exciton is suppressed, and blue phosphorescence emission is achieved. The phosphorescence lifetime at the emission wavelength of 470nm is 315.73ms, and the phosphorescence quantum yield can reach 12.4%, which is successfully used for single-mode information encryption and pattern anti-counterfeiting.

[0005] Although RTP CDs are conveniently used in low-level anti-counterfeiting in the anti-counterfeiting field, they have limited performance in multi-coding anti-counterfeiting applications that require complex optical signals due to their single luminescence type and relatively simple functionality, and are therefore easily imitated. In the field of long afterglow displays, although RTP CDs have a long lifespan, the luminescence duration may still be insufficient to meet the needs of complex time-resolved detection or multimodal applications.

[0006] Therefore, it is very necessary to prepare a carbon dot-based composite material with dual afterglow (RTP, TADF) and a long afterglow lifetime and visible time to the naked eye. Its unique long afterglow luminescence characteristics, multimodal luminescence performance and environmental friendliness not only make it an ideal choice for the new generation of anti-counterfeiting materials, but also increase the complexity and reliability of anti-counterfeiting, and its practical applications are more extensive. Summary of the invention

[0007] The purpose of the present invention is to provide a fluorine-doped long-life double afterglow carbon dot-based composite material and a method for preparing the composite material in order to solve the problem that the existing room temperature phosphorescent carbon dots used for anti-counterfeiting are easily imitated and have a short afterglow lifetime.

[0008] The fluorine-doped long-life dual afterglow carbon dot-based composite material of the present invention is a composite material obtained by reacting boric acid as a coating matrix with fluorine-doped carbon dots after being uniformly dispersed in an aqueous solution, wherein the fluorine-doped carbon dots are prepared by a solvothermal method in an ethanol solvent using folic acid as a carbon source and ammonium fluoride as a dopant.

[0009] More specifically, the fluorine-doped long-life dual afterglow carbon dot-based composite material of the present invention is preferably coated with 1 to 1.5 wt % of fluorine-doped carbon dots.

[0010] The fluorine-doped long-life dual afterglow carbon dot-based composite material prepared by the present invention is a light yellow powder. The fluorine-doped carbon dots are uniformly coated by a boric acid-coated matrix. The composite material exhibits dual afterglow characteristics of room temperature phosphorescence (RTP) and delayed fluorescence (DF) at different excitation wavelengths.

[0011] Specifically, the composite material emits blue fluorescence under 265nm ultraviolet light, and produces blue delayed fluorescence after the excitation light source stops irradiating, which is visible to the naked eye for 11 seconds; it emits blue fluorescence under 365nm ultraviolet light, and produces green phosphorescence after the excitation light source stops irradiating, which is visible to the naked eye for 13 seconds.

[0012] Furthermore, the present invention also provides a method for preparing the fluorine-doped long-life dual afterglow carbon dot-based composite material, which is to dissolve folic acid and ammonium fluoride in ethanol and perform a solvent thermal reaction to obtain a CDs solution, which is mixed with a boric acid solution for reaction and dried to prepare the fluorine-doped long-life dual afterglow carbon dot-based composite material.

[0013] Furthermore, in the above preparation method of the present invention, the molar mass ratio of folic acid to ammonium fluoride is preferably 1:(1-12.5).

[0014] Furthermore, in the above preparation method, the solvent thermal reaction is preferably carried out at 140 to 240° C., and the reaction time is preferably 2 to 10 hours.

[0015] The present invention also purifies the CDs solution obtained by the solvent thermal reaction. The purification treatment means include various conventional methods such as centrifugation, microporous membrane filtration, dialysis, etc., to obtain a pure CDs solution with uniform particle size.

[0016] More specifically, in the present invention, after mixing the CDs solution with the boric acid solution, ultrasonic means can be used to fully mix them.

[0017] The present invention preferably reacts the mixed solution at 170-180° C. and dries to prepare a fluorine-doped long-life double afterglow carbon dot-based composite material.

[0018] In view of the problems that the current RTP CDs used for anti-counterfeiting are easy to imitate and have a short afterglow life, the present invention uses folic acid as a carbon source, ammonium fluoride as a dopant, ethanol as a solvent, and boric acid as a coating matrix, and adopts a solvothermal method to prepare a fluorine-doped long-life double afterglow carbon dot-based composite material. The composite material has a carbon dot-matrix composite structure. On the one hand, boric acid is used as a matrix to produce a glassy state to prevent the triple excitons of CDs from being consumed by non-radiation. On the other hand, fluorine atoms are doped to form highly polarized C-F bonds to adjust the surface electronic state and conformation of CDs, so that hydrogen bonds are formed between the carbon dots and the matrix, and non-radiative transitions are suppressed, thereby enhancing afterglow emission.

[0019] The long-life dual afterglow carbon dot-based composite material prepared by the present invention has good dual afterglow performance, can be used as an afterglow material, and is widely used in technical fields such as optoelectronic devices, graphic anti-counterfeiting and information encryption. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are actual photos of fluorine-doped long-life dual afterglow carbon dot-based composite materials under the irradiation of fluorescent lamps and 265, 365nm ultraviolet lamps and at different times after the ultraviolet lamps are turned off.

[0021] Figure 2 These are the TEM and HRTEM images of fluorine-doped CDs and fluorine-doped long-life double afterglow carbon dots-based composites.

[0022] Figure 3 It is the XRD spectrum of fluorine-doped long-life double afterglow carbon dot-based composite material.

[0023] Figure 4 This is the FT-IR spectrum of the fluorine-doped long-life double afterglow carbon dot-based composite material.

[0024] Figure 5 It is the XPS spectrum of fluorine-doped long-life double afterglow carbon dot-based composite materials and its high-resolution C1s spectrum, B1s spectrum and O1s spectrum.

[0025] Figure 6 It is the excitation spectrum of fluorine-doped long-life double afterglow carbon dots-based composite material.

[0026] Figure 7 The fluorescence and afterglow emission spectra of fluorine-doped long-life double afterglow carbon dots based composite materials.

[0027] Figure 8 This is a comparison chart of the fluorescence and afterglow spectra of the fluorine-doped long-life double afterglow carbon dot-based composite material at excitation wavelengths of 265 and 365 nm.

[0028] Fig. 9 This is the afterglow lifetime diagram of fluorine-doped long-life double afterglow carbon dot-based composite material under 265 and 365nm excitation.

[0029] Fig.10 This is the afterglow lifetime diagram of the undoped fluorine double afterglow carbon dot-based composite material under 265 and 365nm excitation. Implementation

[0030] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0031] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0032] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0033] Example 1

[0034] 44.14 mg of folic acid and 37.04 mg of ammonium fluoride were weighed and mixed evenly with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 160° C. for 6 h.

[0035] After the reaction, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution, which was recorded as F,N-CDs.

[0036] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. The mixed solution is placed in an oven and heated at 180 °C for 5 h. The reaction product is ground to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder, which is recorded as F,N-CDs@BA.

[0037] Figure 1 Actual pictures of the above-prepared fluorine-doped long-life dual afterglow carbon dot-based composite material under the irradiation of a fluorescent lamp and 265 and 365 nm ultraviolet lamps, as well as at different times after the ultraviolet irradiation is stopped, are given.

[0038] The figure shows that the composite material is a light yellow solid under fluorescent light, while under 265nm ultraviolet light, the composite material can emit blue fluorescence and blue delayed fluorescence, and the delayed fluorescence is visible to the naked eye for 11 seconds; under 365nm ultraviolet light, the composite material can emit blue fluorescence and green phosphorescence, and the phosphorescence is visible to the naked eye for 13 seconds.

[0039] Figure 2TEM and HRTEM images (upper right box) of the above-prepared CDs (a) and the fluorine-doped long-life double afterglow carbon dot-based composite material (b).

[0040] It can be seen from the TEM image that the CDs are in the form of small single particles, evenly dispersed, and without agglomeration. In comparison, the CDs in the fluorine-doped long-life double afterglow carbon dot-based composite material are uniformly coated with a boric acid matrix, which not only makes the distribution more uniform, but also the aggregation between particles seems to be effectively suppressed, indicating that the boric acid matrix may play an isolating role to prevent the agglomeration of CDs.

[0041] Further, the HRTEM image of CDs shows that it has obvious lattice fringes with a lattice spacing of 0.21nm, corresponding to the (100) crystal plane of graphite carbon, indicating that CDs have a certain degree of graphitized structure. Lattice fringes can still be observed in the HRTEM image of the composite material after coating, and the lattice spacing is also 0.21nm, indicating that the graphitized structure of CDs has not changed significantly after coating with the boric acid matrix, and the matrix has a good protective effect on the lattice structure of CDs.

[0042] from Figure 3 The XRD spectrum of the fluorine-doped long-life double afterglow carbon dot-based composite material further shows that the diffraction peak at 2θ=23.00° corresponds to the graphite (002) crystal plane, while the diffraction peaks at 2θ=14.70°, 27.75°, and 41.58° correspond to the characteristic fingerprint peaks of B2O3, indicating the presence of B2O3 structure in the composite material. During the heating process, the BA solution gradually transforms into B2O3. The formation of the B2O3 rigid matrix can fix and rigidly protect F, N-CDs, inhibit the non-radiative vibration rotation of F, N-CDs, and isolate the external oxygen, moisture, etc. from the F, N-CDs. T 1, and achieve the quenching of F,N-CDs T 1 stabilization.

[0043] Figure 4 In the FT-IR spectrum of the fluorine-doped long-life double afterglow carbon dot-based composite material, the -1 The broad peak at 1625 cm -1 The peak at 1480 cm-1 is derived from the stretching vibration of CO. -1 The characteristic peak at 1214 cm -1 The characteristic peaks at 735 and 655 cm are derived from the stretching vibration of CF, proving that the F element has been successfully incorporated into CDs. -1The characteristic peaks at 1000 nm are derived from the stretching vibration of BC and the bending vibration of BOH, which further indicates that during the heating process of BA aqueous solution, BA gradually dehydrates and may form a B2O3 matrix, and F, N-CDs are embedded in the matrix through the formation of BC covalent bonds. The BC covalent bonds can fix F, N-CDs and inhibit their non-radiative vibration and rotation, while the inorganic glass matrix can isolate the external oxygen and water from T The quenching of 1 provides rigid protection for F,N-CDs, which is beneficial to the generation of its afterglow.

[0044] Figure 5 The XPS spectra (a) and high-resolution C1s spectra (b), B1s spectra (c) and O1s spectra (d) of fluorine-doped long-lifetime double afterglow carbon dots-based composite materials are given. F,N-CDs@BA is composed of C, B, O, N, and F elements. The characteristic peaks of C1s high-resolution XPS spectrum at 286.6, 285.7, 286.9, and 289.1 eV are derived from CC / C=C, CO / CN, C=O / C=N, and CF bonds. The formation of CF proves that F elements are doped into CDs; the characteristic peaks of B1s high-resolution XPS spectrum at 192.8, 193.8, and 194.7 eV are attributed to BCO2, B2O3, and BO, respectively; the O1s high-resolution XPS spectrum is composed of three characteristic peaks at 532.2 eV (C=O), 533.8 eV (OH / CO), and 534.7 eV (O=CO). The above results indicate that during the heating process, BA undergoes a dehydration reaction to form a B2O3 matrix, achieving rigid protection for F,N-CDs, which is consistent with the characterization results of XRD and FTIR.

[0045] Figure 6 It is the afterglow excitation spectrum of the fluorine-doped long-life double afterglow carbon dot-based composite material, and its optimal excitation wavelengths are 265nm and 365nm.

[0046] Figure 7 The fluorescence emission spectrum (a) and afterglow emission spectrum (b) of the fluorine-doped long-life double afterglow carbon dot-based composite material under different wavelength excitation. The fluorescence emission spectrum of (a) is excitation independent. As the excitation wavelength increases, the emission wavelength is 430nm, which also proves that the composite material has a single luminescence center. Comparing the fluorescence emission and afterglow emission spectra under the same excitation wavelength, if the afterglow emission wavelength is close to the fluorescence emission wavelength, it is delayed fluorescence emission, and if the afterglow emission wavelength is red-shifted compared to the fluorescence emission wavelength, it is phosphorescence emission. Under excitation of 265-325nm, the afterglow emission wavelength of the composite material is close to the fluorescence emission wavelength, both of which are 430nm, which is delayed fluorescence emission; under excitation of 325-385nm, the afterglow emission wavelength is red-shifted compared to the fluorescence emission wavelength, reaching 510nm, which is phosphorescence emission.

[0047] Figure 8 The fluorescence and afterglow emission spectra of the fluorine-doped long-life double afterglow carbon dot-based composite material at excitation wavelengths of 265nm (a) and 365nm (b) are further compared. (a) Under 265nm excitation, the afterglow emission wavelength is close to the fluorescence emission wavelength, proving that it has delayed fluorescence properties; (b) Under 365nm excitation, the afterglow emission wavelength is red-shifted compared to the fluorescence emission wavelength, proving that it has phosphorescent properties.

[0048] Fig. 9 These are the afterglow lifetime diagrams of the fluorine-doped long-life double afterglow carbon dot-based composite material under excitation at 265nm (a) and 365nm (b), respectively. It can be seen that its delayed fluorescence lifetime is 1.21s and its phosphorescence lifetime is 0.47s.

[0049] Among the carbon dot-based double afterglow materials that have been reported so far, the delayed fluorescence lifetime is mostly concentrated around 0.1 to 1.0 s, and those that can reach more than 1 s are relatively rare. The fluorine-doped long-life double afterglow carbon dot-based composite material of the present invention has a delayed fluorescence lifetime of 1.21 s and has a good phosphorescence lifetime, indicating that the material has excellent double afterglow properties and is suitable for use in optoelectronic devices, security and anti-counterfeiting and other fields.

[0050] Example 2

[0051] 44.14 mg of folic acid and 27.78 mg of ammonium fluoride were weighed and mixed evenly with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 160° C. for 6 h.

[0052] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0053] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder.

[0054] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. The solid was observed to emit blue delayed fluorescence, which was visible to the naked eye for 7 seconds; after irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and the solid was observed to emit green phosphorescence, which was visible to the naked eye for 9 seconds.

[0055] Example 3

[0056] 44.14 mg of folic acid and 46.30 mg of ammonium fluoride were weighed and mixed with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 160° C. for 6 h.

[0057] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0058] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder.

[0059] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. The solid was observed to emit blue delayed fluorescence, which was visible to the naked eye for 7 seconds; after irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and the solid was observed to emit green phosphorescence, which was visible to the naked eye for 10 seconds.

[0060] Example 4

[0061] 44.14 mg of folic acid and 3704 mg of ammonium fluoride were weighed and mixed evenly with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 140° C. for 6 h.

[0062] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0063] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder.

[0064] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. The solid was observed to emit blue delayed fluorescence, which was visible to the naked eye for 8 seconds; after irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and the solid was observed to emit green phosphorescence, which was visible to the naked eye for 12 seconds.

[0065] Example 5

[0066] 44.14 mg of folic acid and 37.04 mg of ammonium fluoride were weighed and mixed with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 180° C. for 6 h.

[0067] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0068] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder.

[0069] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. The solid was observed to emit blue delayed fluorescence, which was visible to the naked eye for 11 seconds; after irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and the solid was observed to emit green phosphorescence, which was visible to the naked eye for 9 seconds.

[0070] Example 6

[0071] 44.14 mg of folic acid and 37.04 mg of ammonium fluoride were weighed and mixed evenly with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 160° C. for 2 h.

[0072] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0073] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder.

[0074] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. The solid was observed to emit blue delayed fluorescence, which was visible to the naked eye for 9 seconds; after irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and the solid was observed to emit green phosphorescence, which was visible to the naked eye for 9 seconds.

[0075] Example 7

[0076] 44.14 mg of folic acid and 37.04 mg of ammonium fluoride were weighed and mixed with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 160° C. for 10 h.

[0077] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0078] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain fluorine-doped long-life double afterglow carbon dot-based composite material powder.

[0079] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. The solid was observed to emit blue delayed fluorescence, which was visible to the naked eye for 8 seconds; after irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and the solid was observed to emit green phosphorescence, which was visible to the naked eye for 11 seconds.

[0080] Comparative Example 1

[0081] 44.14 mg of folic acid was weighed and mixed evenly with 15 mL of ethanol to obtain a reaction solution, which was placed in a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and subjected to a solvent thermal reaction at 160° C. for 6 h.

[0082] After the reaction was completed, the reaction solution was cooled to room temperature, centrifuged to obtain the supernatant, placed in a rotary evaporator, and rotary evaporated at 65°C to remove ethanol. 5 mL of deionized water was added to dissolve the product, filtered with a 0.22 μm microporous filter membrane, and transferred to a 500 Da dialysis bag for 24 h to obtain a CDs solution.

[0083] Weigh 2 g of BA powder, dissolve it in 40 mL of deionized water, and mix it evenly by ultrasonication for 30 min. Then add 5 mL of CDs solution and continue ultrasonication for 30 min. Place the mixed solution in an oven and heat it at 180 °C for 5 h. Grind the reaction product to obtain a fluorine-free double afterglow carbon dot-based composite material powder.

[0084] The powdered solid obtained above was irradiated with a 265nm ultraviolet lamp for 3 to 5 seconds, and then the irradiation was stopped. It was observed that the solid emitted blue delayed fluorescence, which was visible to the naked eye for 5 seconds, which was significantly shorter than that in Example 1. After irradiation with a 365nm ultraviolet lamp for 3 to 5 seconds, the irradiation was stopped, and it was observed that the solid emitted green phosphorescence, which was visible to the naked eye for 6 seconds, which was also significantly shorter than that in Example 1.

[0085] Further testing of the afterglow lifetime of the solid under 265nm and 365nm excitation showed the following results: Fig.10 , its delayed fluorescence lifetime is 426.11ms, and its phosphorescence lifetime is 196.62ms.

[0086] Comparative Example 1 shows that the delayed fluorescence lifetime of the fluorine-doped long-lifetime dual afterglow carbon dot-based composite material is 1.21 s, and the phosphorescence lifetime is 0.47 s, which fully demonstrates that fluorine doping can effectively prolong the life of the afterglow material, and the afterglow performance of the material prepared in Example 1 is better.

[0087] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A fluorine-doped long-life dual afterglow carbon dot-based composite material, which is a composite material obtained by reacting boric acid as a coating matrix with fluorine-doped carbon dots after being uniformly dispersed in an aqueous solution, wherein the fluorine-doped carbon dots are prepared by a solvothermal method in an ethanol solvent using folic acid as a carbon source and ammonium fluoride as a dopant, and produce blue delayed fluorescence at an excitation wavelength of 265nm and green phosphorescence at an excitation wavelength of 365nm.

2. The fluorine-doped long-life dual afterglow carbon dot-based composite material according to claim 1, characterized in that The fluorine-doped long-life double afterglow carbon dot-based composite material is coated with 1 to 1.5 wt % of fluorine-doped carbon dots.

3. The method for preparing the fluorine-doped long-life dual afterglow carbon dot-based composite material according to claim 1 is to dissolve folic acid and ammonium fluoride in ethanol and perform a solvent thermal reaction to obtain a CDs solution, which is mixed with a boric acid solution for reaction and dried to prepare the fluorine-doped long-life dual afterglow carbon dot-based composite material.

4. The preparation method according to claim 3, characterized in that The molar mass ratio of folic acid to ammonium fluoride is 1:(1-12.5).

5. The preparation method according to claim 3, characterized in that The solvent thermal reaction is carried out at 140-240°C.

6. The preparation method according to claim 5, characterized in that The solvent thermal reaction time is 2 to 10 hours.

7. The preparation method according to claim 3, characterized in that The mixed reaction temperature is 170-180°C.

8. Use of the fluorine-doped long-life dual afterglow carbon dot-based composite material as claimed in claim 1 in the preparation of optoelectronic devices as an afterglow material.

9. Use of the fluorine-doped long-life double afterglow carbon dot-based composite material as claimed in claim 1 as an anti-counterfeiting material in laser anti-counterfeiting.

Citation Information

Patent Citations

  • Preparation method of doped fluorine ion carbon dot and application thereof

    CN107529514A

  • Method for preparing full-spectrum fluorescent carbon dots by using one-pot method

    CN110982517A

  • Long afterglow material, and preparation method and application thereof

    CN111154480A

  • Color-adjustable fluorescent and phosphorescent carbon dot material as well as preparation method and application thereof

    CN113773836A

  • Method of preparing aerogel blanket

    KR1020220053213A